Corporate social responsibility, board gender diversity and real earnings management: The case of Jordan - Belal Ali Abdulraheem Ghaleb; Sumaia Ayesh Qaderi; Ahmad Almashaqbeh; Ameen Qasem (Cogent Business & Management, 2021)
This study examines the relationship between corporate social responsibility (CSR) reporting, board gender diversity (BGEND) and real earnings management (REM). It also investigates how the relationship between CSR reporting and REM differs between gender-diverse and non-diverse firms. Content analysis was used to measure CSR reporting. The ordinary least square regression is used to examine the relationships for a sample of 475 firm-year observations listed on the Amman Stock Exchange during 2011-2016. The results show that CSR reporting is significantly and negatively associated with REM in the Jordanian market. Nevertheless, BGEND is negatively and significantly related to REM. More importantly, the results show that BGEND moderates the CSR-REM relationship. Further, when the sample is split into board gender-diverse and non-diverse firms, the CSR-REM significant negative relationship is evident only in the former, corroborating the moderating role of the BGEND in Jordan. This study contributes to the literature on CSR, BGEND, and REM by offering evidence for the moderating role of BGEND on the CSR-REM relationship, supporting the view that females are more sensitive to ethics. Regulators and stakeholders should be aware of the potential effect of engagement in CSR reporting and the benefits of having a gender-diverse board on financial reporting quality.
Keywords: 650; corporate social responsibility; real earnings management; board gender diversity; female directors; corporate governance; Jordan